Optimization of fluidized bed drying of Lactiplantibacillus plantarum grown in sustainable culture media for winemaking application - Navarro, Marina E.; Morales, Manuel A.; Brizuela, Natalia S.; Caballero, Adriana C.; Reyes-Urrutia, Andrés; Vicente, Fausto; Semorile, Liliana C.; Bravo-Ferrada, Bárbara M.; Tymczyszyn, Emma E. (Frontiers in Microbiology, 2025)
Lactic acid bacteria (LAB) play a key role in winemaking by driving malolactic fermentation, which enhances microbial stability and reduces wine acidity. To enable the large-scale development of LAB starter cultures, cost-effective biomass production and preservation methods are required. Traditional preservation techniques, such as freeze-drying, can be expensive and energy-intensive. Therefore, this study explored fluidized bed drying as a sustainable and low-cost alternative for preserving Lactiplantibacillus plantarum UNQLp 11 cultured in apple pomace (AP) and whey permeate (WP)-based media, with emphasis on maintaining malolactic activity after preservation. L. plantarum UNQLp 11 was cultivated in AP- and WP-based media and subjected to fluidized bed drying at 45 °C and 60 °C. Drying times and culture conditions (pH, medium composition) were varied to assess their impact on cell viability. After drying, the samples were stored for 12 months at 4 °C to evaluate long-term stability. Water activity (aw) was monitored and adjusted between 0.10 and 0.33. Malolactic activity was tested through winemaking trials using synthetic and Malbec wines, both with and without rehydration in DeMan-Rogosa-Sharpe (MRS) broth. Fluidized bed drying caused viability reductions of 3–5 log units, with survival rates influenced by medium composition, pH, and drying duration. Optimal results were achieved at 45 °C for 35 min, yielding final counts of 8.3 log CFU/g in WP cultures and 7.0–7.4 log CFU/g in AP cultures. After 12 months of storage at 4 °C, viability losses were limited to approximately 1 log unit when aw values were maintained between 0.10 and 0.33. In winemaking assays, WP-derived cultures preserved malolactic activity, consuming 70–100 % of malic acid in synthetic wine and up to 80 % in Malbec wine. AP cultures required rehydration to restore performance, reaching 75–100 % and 50–80 % malic acid consumption in synthetic and Malbec wines, respectively. The results demonstrate that fluidized bed drying is a viable and energy-efficient alternative to freeze-drying for preserving L. plantarum UNQLp 11. Cultures produced in WP medium exhibited superior viability and maintained malolactic functionality after long-term storage. However, AP-based cultures required rehydration to regain full activity. These findings highlight the potential of fluidized bed drying for sustainable LAB preservation in winemaking applications, although further optimization of drying parameters and protective agents is needed to enhance industrial applicability.